Development Of SMR Training Model in Forehand Tennis Groundstroke Technique Aged 14-16 Years - Muhammad Ali Ode; Firmansyah Dlis; Oman Unju Subandi (Universitas Negeri Semarang, 2025)
The quality of forehand groundstroke training is a crucial aspect in improving the performance of junior tennis athletes. However, structured and tailored training models that address the specific needs of athletes aged 14–16 are still limited, especially in training centres such as SRTC Jakarta. This study aims to develop an innovative and applicable forehand groundstroke training model to assist coaches and athletes in enhancing training effectiveness and playing performance. The research employed a Research and Development (R&D) approach based on the ten-step Borg & Gall model, including information gathering, planning, initial product development, preliminary field testing, product revision, main field testing, operational revision, operational field testing, final product revision, and dissemination. The developed model consists of 25 forehand groundstroke training variations, including Shadow, Multiball, and Rally exercises, which were validated by experts. The study was conducted at SRTC, Jakarta, from October to December 2023, using a pretest-post-test control group design. Data were analysed using descriptive statistics, t-tests, and the N-Gain Score to measure the model’s effectiveness. The results indicate that the developed training model is valid in content, effective in improving forehand groundstroke skills, and applicable in the context of junior athlete training. The study concludes that the developed model significantly enhances the quality of training and technical performance of forehand groundstrokes in junior tennis athletes aged 14–16. The novelty of this research lies in the development of a varied and empirically tested forehand groundstroke training model tailored to the specific needs of junior athletes, offering a systematic and targeted training guide for early-stage athlete development.